Assessment of biomass burning impact on the regional air quality of Yangtze River Delta, China - Xu, Jingsha (2018)
Yangtze River Delta (YRD) region experiences severe haze pollution as a result of rapid economy growth and urbanization during recent decades. Its annual average PM2.5 (particulate matter with aerodynamic diameter ≤ 2.5μm) concentration often exceeded the National Ambient Air Quality Standards of China–Grade II (35 µg m-3) and this occurs not only in urban areas but also in suburban and rural areas as well. One of the major contributors to the decreasing air quality in this region is biomass burning. Hence, this research aims to study biomass burning impact on the air quality in YRD through the investigation of atmospheric fine aerosols. An intensive field sampling campaign was conducted at four representative sampling sites in urban, suburban and rural areas of this region from December 2014 to November 2015. The characteristics of PM2.5 samples that collected in this region were investigated through a comprehensive analysis of major components of aerosol samples, including major water soluble inorganic ions (WSII), trace metals, organic carbon (OC), elemental carbon (EC), polycyclic aromatic hydrocarbons (PAHs), biomass burning tracers and fungal spore tracers. The investigation of above mentioned components can provide a very comprehensive profile of PM2.5-related pollutants in YRD. In addition, air mass backward trajectory analysis and fire-spots analysis were also carried out in this study to identify air mass origins, pathways and fire events in this region. Positive matrix factorization (PMF) was also applied to estimate the contribution from biomass burning to fine aerosols in YRD. Both temporal and spatial trends of above pollutants were studied accordingly to set up seasonal and geographical profiles. In total, more than 240 PM2.5 samples were being analysed in this study. The annual average PM2.5 concentration in this region was 66.2 ± 37.7 µg m-3, and urban sites were observed with higher PM2.5 concentrations than the other two suburban and rural sites. The annual average concentration of total 12 WSII in YRD was 29.1 ± 19.9 µg m-3, dominated by SO42-, NO3-, NH4+, Cl-, and K+. The annual averaged concentration of total 20 metals in YRD was 2.8 ± 0.4 μg m-3, dominated by K, Al, Fe, Mg, Zn and V (> 100 ng m-3). The carcinogenic risk of Cr and As via ingestion is higher than the acceptable level for all residences in YRD. The annual average level of PM2.5-associated total carbon (TC) at YRD region was 14.3 ± 4.1 μg m-3, accounted for 26.2 (± 6.5) % of annual mean PM2.5 concentration. The annual averaged concentration of total 17 PAHs in YRD was 35.5 ± 12.3 ng m-3, dominated by retene, BkF, BbF, Ind, Bpe, Flt and Chr (> 2 ng m-3). The annual lifetime cancer risk of PAHs through inhalation exposure in YRD was 3.57 × 10-4. The annual average concentrations of levoglucosan and arabitol were 81.3 ± 18.2 ng m-3 and 5.6 ± 0.7 ng m-3 respectively. These compounds above exhibited similar seasonal patterns as PM2.5 with elevated level in winter and lower level in summer, except fungal spore tracers which showed the highest concentration in summer. In total, WSII, trace metals, TC, PAHs and organic tracers explained more than 69.8 % of total PM2.5 in YRD. The contribution from biomass burning to fine aerosols in YRD was 18.2%-37.4%. The concentration of biomass burning emitted PM2.5 ranged from 10.07 μg m-3 in spring to 27.60 μg m-3 in winter. Fine aerosols in southern YRD were contributed remarkably by fuel combustion such as coal and biomass burning, with less contributions from traffic emissions and soil origins, minor from sea salts. The contribution from coal combustion and biomass burning was more significant in winter and autumn than in spring and summer. The contribution from biomass burning decreased within the provincial capital municipality and the influence from biomass burning was more significant in rural area during autumn. In addition, the air mass backward trajectory analysis also showed that the contribution from transboundary transport of aerosols from highly polluted north China cannot be neglected.